Mary Contini: Dear Francesca: A Cookbook with Love - Hall, Aileen (Petits Propos Culinaires, 2024)
Mary Contini: Dear Francesca: A Cookbook with Love: Ebury Press, London 2002: ISBN 0091881765: 352 pp, sepia photos., index, h/b, £20.